Exploring the Backyard of nCOVID: Determinants of death toll in pandemics - Rajesh Gupta; Smita Trivedi (ACHSM, 2020)
Heterogeneity in number of deaths in different countries during the ongoing nCOVID crisis challenged us to look for determinants of pandemic death toll across the world. Using the past two decades data of pandemic deaths in the world, this study considered if engagement in international trade, health care expenditure and population density have any impact on the pandemic death toll. Using linear regression model controlled for types of disease, we not only found trade significantly impacting death toll, but also surprisingly found positive correlation between share of healthcare expenditure in GDP and fatalities in pandemics. Our findings suggest that policy intervention is required for mitigating health impacts of trade and 'tweaking' the health expenditure towards pandemic prevention.